Variability of Corynespora cassiicola in pathogenicity toxin production, response to fungicides and molecular aspects - Joseph A; George Ginu; Jacob C K; Philip S; Zacharia Cina Ann (National Symposium on Crop Surveillance: Disease Forecasting and Management: Souvenier & Abstracts, 19-21 February 2004, New Delhi)
An attempt was made to study variability among 16 isolates of Corynespora cassiicola affecting Hevea brasiliensis in relation to their pathogenicity, toxin production, response to fungicides and molecular aspects. Pathogenicity studies in two clones viz RRII 105 (susceptible clone) and GT 1 (tolerant clone) revealed variations. Similar results were obtained for toxin production when estimated by leaf wilting bioassay using crude culture filtrate. Percentage of wilting of the leaves was high in culture filtrate from the more pathogenic isolates. The results revealed a positive correlation between pathogenicity and quantity of toxin produced by an isolate. All the isolates were highly sensitive to carbendazim even at the lowest concentration tested (5ppm) except the isolate Nos. 2 and 15. The isolate 2 showed 88.8 and 94.4;inhibition and isolate 15 showed 83.3 and 93.3;inhibition at 15 and 5ppm respectively. The response of isolates to mancozeb was highly variable. RAPD analysis of the isolates clearly indicated existence of 3 distinct genetic patterns of C.cassiicola. The isolates 2,3 and 17 showed different RAPD profiles from others in all the primers tested. However this difference in molecular characters could not be correlated to the variation in pathogenecity, toxin production and in response of the isolates to fungicides.
Keywords: Corynespora cassiicola; Pathogenicity; Toxin production